2018 Design, Automation &Amp; Test in Europe Conference &Amp; Exhibition (DATE) 2018
DOI: 10.23919/date.2018.8342006
|View full text |Cite
|
Sign up to set email alerts
|

Buffer-aware bounds to multi-point progressive blocking in priority-preemptive NoCs

Abstract: Abstract-This paper aims to reduce the pessimism of the analysis of the multi-point progressive blocking (MPB) problem in real-time priority-preemptive wormhole networks-on-chip. It shows that the amount of buffering on each network node can influence the worst-case interference that packets can suffer along their routes, and it proposes a novel analytical model that can quantify such interference as a function of the buffer size. It shows that, perhaps counter-intuitively, smaller buffers can result in lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(59 citation statements)
references
References 11 publications
0
57
0
Order By: Relevance
“…Nonetheless, for the sake of completeness of this work, we will compare our approach against both SOT A and SOT A + . A more detailed explanation of these methods is given in Section 5, and for further details the reviewer is advised to consult the work of Indrusiak et al (2018).…”
Section: Related Workmentioning
confidence: 99%
“…Nonetheless, for the sake of completeness of this work, we will compare our approach against both SOT A and SOT A + . A more detailed explanation of these methods is given in Section 5, and for further details the reviewer is advised to consult the work of Indrusiak et al (2018).…”
Section: Related Workmentioning
confidence: 99%
“…The communication between the cores and the router is made by two unidirectional links (one from c to r and other from r to c). In this work, we have applied the widely used 2D-mesh topology [2][8] [9], considering wormhole NoCs with priority-preemptive arbitration, widely studied in the literature due to their ability to provide resources for hard real-time guarantees [9] [16].…”
Section: Performance Analysis For Nocsmentioning
confidence: 99%
“…In this paper, we have applied the endto-end schedulability analysis presented in [8], which ensures all tasks executing over a processing core and their respective packets low over a NoC will meet their deadlines even in the worst-case scenario. For the analysis of packet lows, we incorporated the improvements from [9], which consider the impact of inite bufers, low control backpressure, and multi-point progressive blocking in priority-preemptive NoCs. For a comprehensive review on NoC performance analysis, see [10].…”
Section: Performance Analysis For Nocsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, authors in [45] have shown that the model proposed in [37] and later enhanced [16] has some deficiencies. Based on the findings in [45], authors in [14] have proposed a tight alternative model for prioritypreemptive real-time networks. Best-effort wormhole NoCs can also be employed in the context of hard-real time systems by deriving latency upperbounds as described in [31].…”
Section: Related Workmentioning
confidence: 99%